Glacial-interglacial variations in the neodymium isotope composition of seawater in the Bay of Bengal recorded by planktonic foraminifera - Burton, K; Vance, D (2000)
This study presents neodymium isotope and elemental data for cleaned planktonic foraminifera from ODP site 758 in the southernmost reaches of the Bay of Bengal in the north-east Indian Ocean. Cleaning experiments using oxidative-reductive techniques suggest that diagenetic Fe-Mn oxyhydroxide coatings can be effectively removed, and that the measured Nd isotope composition reflects the composition of seawater from which the foraminiferal calcium carbonate was precipitated. Modern core-top Pulleniatina obliquiloculata and Globorotalia menardii give ε(Nd) values of -10.12±0.16 and -10.28±0.16, respectively, indistinguishable from recent direct measurements of surface seawater in this area. A high-resolution Nd isotope record obtained from G. menardii for the past 150 kyr shows systematic variations (Δε(Nd)~3) on glacial-interglacial timescales. The timing of those variations shows a remarkable correspondence with the global oxygen isotope record, which suggests a process controlling the Nd isotope composition that responds in phase with global climate cycles. Palaeoclimate reconstruction indicates that during the last glacial maximum changes in monsoon circulation resulted in a reduction in rainfall over the Indian subcontinent, and a decrease in the flux of river water delivered to the Bay of Bengal. Thus, changes in the riverine input of Nd, a change in either flux or composition, most likely caused the isotope variations, although changes in dust source or local ocean circulation may have also played a role. These results clearly establish a link between climate change and variations in radiogenic isotopes in the oceans, and illustrate the potential of Nd isotopes in foraminifera for high-resolution palaeoceanographic reconstruction. (C) 2000 Elsevier Science B.V. All rights reserved.